Effect of silica fume and basalt fibers on the fracture parameters of magnesium phosphate cement incorporating fly ash - Pehlivan, Ahmet Onur (Revista de la Construcción. Journal of Construction, 2022)
Magnesium phosphate cements are implemented for several purposes demonstrating significant mechanical properties in limited durations. However, brittle behavior of this material needs utmost concern and tensile performance may be enhanced with the proper application of fibers increasing both ductility and energy absorption capacity. This research studies the effect of basalt fibers (BF) and silica fume (SF) on the fracture parameters of magnesium phosphate cement (MPC). MPC mortar mixtures were prepared with different SF (0, 5, 10%) and BF amounts (0, 0.5, 0.75, 1 % by wt.). Also fly ash was adopted with a constant ratio for all mixes. Compressive strength and splitting tensile strength results indicated that addition of SF into mixtures extensively developed the matrix structure and improvements were noted with the increasing SF content. The inclusion of BF enhanced the flexural behavior although there were significant improvements in the fracture energy as well as the double-K parameters. Improvements in the tensile capacity of specimens with high BF were prone to the amount of SF percentage such that inclusion of 1 % BF performed best with 10 % SF added mixtures. Load-CMOD (crack mouth opening displacement) curves obtained from notched three-point tests were given for all specimen series and parameters were calculated according to the double-K criterion. Addition of BF resulted in higher toughness values however presence of SF was very significant in establishing appreciable development in toughness values. Brittleness index was implemented to establish clear conclusions on the findings and best performance was seen for specimens with 10% SF and 1% BF.